14‐3‐3 epsilon plays an important role in testicular germ cell apoptosis: A functional proteomic study of experimental varicocele. (5th April 2019) - He, Qing qing; Wu, Xiao; Liu, Xiao peng; Yang, Xiao jian; Yuan, Zhong min; Zhang, Yan
Abstract: The latest perspective indicates that apoptotic dysregulation is an important mechanism in male infertility induced by varicocele. To elucidate the molecular mechanism of apoptosis caused by varicocele, we used proteomics (2D‐MALDI‐TOF MS) to identify the altered proteins in the testes of experimental varicocele rats compared with the control. Here, 21 significantly different protein spots were detected by proteomics technology. 14‐3‐3 epsilon (14‐3‐3ε) was our subsequent research target because of its function in apoptosis. The expression of 14‐3‐3ε in rat testes was confirmed by Western blot and immunohistochemistry, and the terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) method was used to analyse the apoptosis of germ cells. GC‐1 spg cells transfected with small interfering RNA were used to confirm the function of 14‐3‐3ε in vitro. 14‐3‐3ε protein expression decreased, accompanied by a higher apoptosis index in rat testes of the varicocele group. Furthermore, 14‐3‐3ε siRNA‐treated GC‐1 spg cells caused the upregulation of the apoptotic rate detected by flow cytometry. The expression of Bax and Bcl‐2 was found to be regulated by 14‐3‐3ε in vitro. Our investigation demonstrated the pro‐apoptotic function of the downregulation of 14‐3‐3ε, which may play an important role in germ cell apoptosis induced by varicocele.